2017
DOI: 10.3390/ijms18102155
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Amyloidogenic Proteins in the Proteomes of Plants

Abstract: Amyloids are protein fibrils with characteristic spatial structure. Though amyloids were long perceived to be pathogens that cause dozens of incurable pathologies in humans and mammals, it is currently clear that amyloids also represent a functionally important form of protein structure implicated in a variety of biological processes in organisms ranging from archaea and bacteria to fungi and animals. Despite their social significance, plants remain the most poorly studied group of organisms in the field of am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 81 publications
0
29
0
Order By: Relevance
“…Previously, we performed a large-scale bioinformatic analysis of potentially amyloidogenic properties of plant proteins including all annotated proteomes of land plant species [22]. This screening demonstrated that seed storage proteins comprising the evolutionary conservative β-barrel domain Cupin-1 were rich in amyloidogenic regions in the majority of analyzed species [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we performed a large-scale bioinformatic analysis of potentially amyloidogenic properties of plant proteins including all annotated proteomes of land plant species [22]. This screening demonstrated that seed storage proteins comprising the evolutionary conservative β-barrel domain Cupin-1 were rich in amyloidogenic regions in the majority of analyzed species [22].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting category of proteins in the plant prionomes is that of Ts/RTRs, which constitutes 3.4% of the total PrLPs identified from all species. Though prionomes of several organisms have been predicted including those of plants (Antonets and Nizhnikov, 2017) but Ts/RTRs found no mention in any of the previous studies, despite the rice prionome constituting a huge 65% share. Presence of RTRs/Tstype of PrLPs in plants is intriguing, but indications about their prion-like roles have been reported in human and animal brains, where transposon activity plays a potentially important role in the pathogenesis of prion diseases (Mustafin and Khusnutdinova, 2018).…”
Section: Discussionmentioning
confidence: 86%
“…We speculate that plants are simply better at coping with proteostasis than other taxonomic groups, using mechanisms other than high ISD to protect themselves from protein misfolding and aggregation. Plant proteomes are rich in predicted amyloidogenic regions (Antonets & Nizhnikov 2017a), and yet there is a paucity of evidence for aggregate formation in plants under normal conditions (Antonets & Nizhnikov 2017b). This is perhaps due in part to the presence of molecules such as polyphenols, which inhibit aggregation (Velander et al 2017).…”
Section: Discussionmentioning
confidence: 99%